Profile of epileptic patients at a tertiary care centre - Verma, Kushel; Sharma, Dinesh Dutt; Sharma, R. C. (International Journal of Research in Medical Sciences, 2020)
Background: The present study was done in a tertiary care centre of North India to know the profile of epilepsy. Methods: Total of 210 patients were selected during the period August, 2017 to July 2018 who attended outpatient clinic of the Department of Neurology, Indira Gandhi Medical College, Shimla, Himachal Pradesh. Detailed clinical history was taken, general physical examination, and routine blood examination were carried out. Results: Of all the cases, sex ratio (male:female) was 2.39:1. A high proportion of cases (43.3%) were from lower-middle socio-economic group. 76.7% patients had generalized seizures. For 38.6% patients, frequency of seizures was more than 8 in the past 6 months. 71.9% of the patients were using only one anti-epileptic drug. Conclusions: Patients with seizures comprise a significant burden in inpatient department of developing countries.